Electrochemical and surface deformation studies on electrodeposited nanostructured Bi2Te3 thin films. (May 2019) - Thorat, J.B.; Mohite, S.V.; Madake, S.B.; Suryavanshi, R.D.; Rajpure, K.Y.; Shinde, T.J.; Fulari, V.J.; Shinde, N.S.
Highlights: The surface deformation study of nanostructured Bi2 Te3 thin films by DEDHI technique. Structural analysis of Bi2 Te3 thin films. Effects of varying electrolyte solution concentration on physico-chemical properties of Bi2 Te3 thin films. EIS study of synthesized thin films. Abstract: In this article, we have used double exposure digital holographic interferometry (DEDHI) technique for surface deformation study and hologram recording during synthesis of the Bi2 Te3 thin films by electrodeposition method. The synthesized Bi2 Te3 thin films were characterized structural, morphological, electrochemical, wettability and surface deformation study. Further the holograms are recorded during the electrodeposition process by varying the concentration of electrolyte. From the recorded fringes the stress, deposited mass and thickness have been calculated. It is observed that the fringe width, mass of deposited thin films, and stress to substrate changes with the concentration of electrolyte. The DEDHI technique is found more reliable for thickness measurement in electrodeposition process. The EIS study confirms that the deposited material is highly conducting.